Short Communication: Sarocladium oryzae associated with sheath rot disease of rice in Indonesia - Syafiqa Pramunadipta; Ani Widiastuti; Arif Wibowo; Haruhisa Suga; Achmadi Priyatmojo - (Society for Indonesian Biodiversity, 2020)
Abstract. Pramunadipta S, Widiastuti A, Wibowo A, Suga H, Priyatmojo A. 2020. Short Communication: Sarocladium oryzae associated with sheath rot disease of rice in Indonesia. Biodiversitas 21: 1243-1249. One of the obstacles in increasing rice production is the presence of sheath rot pathogen infection, which causes changes in color on the rice sheath to brown or reddish-brown, sometimes does not produce rice grain. The major fungal pathogens that cause sheath rot disease are Sarocladium oryzae and Fusarium spp. The loss of rice yields reaches 85%. The disease found in six provinces, some of which are the largest rice-producing centers in Indonesia. A total of twenty-four Sarocladium sp. were isolated from leaf sheath symptom on potato dextrose agar and water agar medium. Sheath rot pathogen identification based on molecular method was performed using internal transcribed spacer (ITS) rDNA gene sequencing. Necrosis occurs after artificial inoculation in Ciherang rice variety was observed and showed that all isolates were pathogenic. Morphological characterization of the isolates identified them as Sarocladium sp. Molecular identification showed that six representatives isolates belonging to S. oryzae. These findings are important information about the fungal pathogen that causes sheath rot disease in Indonesia, and in studies for formulating control measures of the pathogen in the future to prevent the disease epidemic on rice. This is the first report about the existence of sheath rot disease, morphological characterization and molecular identification of S. oryzae in various rice fields in Indonesia.